EFEKTIVITAS IMPLEMENTASI PERPRES NO. 66 TAHUN 2021 DALAM MEWUJUDKAN KEMANDIRIAN PANGAN BERKELANJUTAN DI PROVINSI LAMPUNG - wati, yonna; maysuhetni, maysuhetni; Islam, Nur; Suprihatin, Suprihatin (DEMOKRASI, 2026)
ABSTRACTLampung Province, as one of Indonesia's national food barns, faces challenges such as production disparities, price fluctuations, and import dependency. Presidential Regulation No. 66 of 2021 concerning the National Food Agency is designed to strengthen food sovereignty, but its implementation at the regional level has not been comprehensively evaluated. This research is urgent to identify the gap between national policy and field realities, and to formulate evidence-based solutions to support sustainable food development. Objectives: (1) To evaluate the effectiveness of implementing Perpres No. 66/2021 in Lampung, (2) To analyze supporting and inhibiting factors for food self-sufficiency, and (3) To formulate adaptive policy recommendations for stakeholders. Methods: The research uses a mixed-methods approach with quantitative analysis (survey of 100 farmers in 5 districts) and qualitative analysis (interviews with 15 stakeholders, FGD). Data were analyzed using descriptive statistics, regression, and thematic analysis. The research results show the effectiveness of policy implementation is in the low-medium category (55%), with main constraints on institutions, coordination, and budget. Although there was an increase in rice production (10%), systemic self-sufficiency has not been achieved. Conclusion: It is necessary to strengthen regional food institutions, increase budget allocation, and a participatory approach to transform the national mandate into effective regional action.Keywords: Policy Implementation; Food Self-Sufficiency; Presidential Regulation No.66 of 2021; Lampung Province; Sustainable Agriculture